2016
DOI: 10.1016/j.ejmech.2016.03.080
|View full text |Cite
|
Sign up to set email alerts
|

A combined in silico / in vitro approach unveils common molecular requirements for efficient BVDV RdRp binding of linear aromatic N-polycyclic systems

Abstract: In this work, we present and discuss a comprehensive set of both newly and previously synthesized compounds belonging to 5 distinct molecular classes of linear aromatic N-polycyclic systems that efficiently inhibits bovine viral diarrhea virus (BVDV) infection. A coupled in silico/in vitro investigation was employed to formulate a molecular rationale explaining the notable affinity of all molecules to BVDV RNA dependent RNA polymerase (RdRp) NS5B. We initially developed a three-dimensional common-feature pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…As described above, the driven idea for this project is the isosteric substitution of a nitrogen atom with a carbon atom and evaluate the antiviral activity of the resulted molecules compared with the parental compounds. Naphthoimidazole derivatives ( 3a -j ) were designed and synthesised in order to confirm the relevance of nitrogen atom in position 5 of the imidazoquinoline derivatives for the interaction with the target, these molecule's antiviral results confirmed the predicted affinity data previously published since they showed a consistent loss of antiviral activity with respect to parental compounds [32]. Derivative 3a still maintains a weak antiviral activity, EC 50 at 16 µM, but related at cytotoxicity CC 50 value of 37 µM.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…As described above, the driven idea for this project is the isosteric substitution of a nitrogen atom with a carbon atom and evaluate the antiviral activity of the resulted molecules compared with the parental compounds. Naphthoimidazole derivatives ( 3a -j ) were designed and synthesised in order to confirm the relevance of nitrogen atom in position 5 of the imidazoquinoline derivatives for the interaction with the target, these molecule's antiviral results confirmed the predicted affinity data previously published since they showed a consistent loss of antiviral activity with respect to parental compounds [32]. Derivative 3a still maintains a weak antiviral activity, EC 50 at 16 µM, but related at cytotoxicity CC 50 value of 37 µM.…”
Section: Resultssupporting
confidence: 60%
“…In detail, arginine 295 interacts with N5 of the lead compound as H-bond donor, while N1 resulted as H-bond acceptor in the interaction with tyrosine 674 and the nitrogen of the benzonitrile moiety gives H-bond with serine 411. Has also been predicted the decrease of affinity of some molecules with the substrate when R295 and Y674 -critical residues for compound binding -are mutated into alanine and the prediction has been confirmed by in vitro assays on the mutant RdRp [32]. In order to have a further negative control for these simulations, we now designed some chemical modification on the lead compounds and parent compounds similarly active in BVDV RdRp inhibition, and we synthesised the designed compounds.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a part of our researches on heterocyclic compounds with antiviral activity (Conti et al, 2014, 2017; Carta et al, 2016; Fioravanti et al, 2017), we recently identified ( N -(1,3-diphenyl-1 H -pyrazol-4-yl)methyl)anilines ( 1a-v ) as a new class of potent and selective inhibitors of human respiratory syncytial virus (RSV) replication (Fioravanti et al, 2015). Some derivatives were also endowed with a moderate activity against YFV and BVDV representative type members of the Flavivirus genus and the Pestivirus genus, respectively, within the Flaviviridae family (Fioravanti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine viral diarrhea-mucosal disease (BVD-MD), also known as bovine viral diarrhea-mucosal disease virus or mucosal virus, is a contagious disease that often occurs in domestic animals[1, 2]. BVD-MD is caused by BVDV viral infection from viruses in the Pestivirus genus of the Flaviviridae family.…”
Section: Introductionmentioning
confidence: 99%